Influence of mechanical site preparation on regeneration success of planted conifers in clearcuts in Fennoscandia – a review - Sikström, Ulf; Hjelm, Karin; Holt Hanssen, Kjersti; Saksa, Timo; Wallertz, Kristina
2020